Proceedings of the 2012 International Symposium on Software Testing and Analysis 2012
DOI: 10.1145/2338965.2336762
|View full text |Cite
|
Sign up to set email alerts
|

Search-based system testing: high coverage, no false alarms

Abstract: Modern test case generation techniques can automatically achieve high code coverage. If they operate on the unit level, they run the risk of generating inputs infeasible in reality, which, when causing failures, are painful to identify and eliminate. Running a unit test generator on five open source Java programs, we found that all of the 181 reported failures were false failures-that is, indicating a problem in the generated test case rather than the program. By generating test cases at the GUI level, our EXS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
78
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 91 publications
(79 citation statements)
references
References 43 publications
0
78
0
Order By: Relevance
“…Note that the problem of implicit preconditions is not specific to SBST, as it is independent of the test generation technique. For example, in a recent study we observed the same problem in Randoop's output [24]: Not a single of the 112 failures on a simple address book application was due to a real fault, but all were caused because Randoop violated the implicit precondition that there can only be one instance of an address book in that application.…”
Section: Real Faults Due To Assertions and Object Contractsmentioning
confidence: 88%
See 1 more Smart Citation
“…Note that the problem of implicit preconditions is not specific to SBST, as it is independent of the test generation technique. For example, in a recent study we observed the same problem in Randoop's output [24]: Not a single of the 112 failures on a simple address book application was due to a real fault, but all were caused because Randoop violated the implicit precondition that there can only be one instance of an address book in that application.…”
Section: Real Faults Due To Assertions and Object Contractsmentioning
confidence: 88%
“…[11]). Alternatively, we are exploring the possibility to drive testing through user interfaces to filter out exceptions that violate the implicit assumptions of the developer [24].…”
Section: Automated Oracles Without Specificationsmentioning
confidence: 99%
“…Andrews [5]. Although not intended for Web applications, Pacheco, et al developed Randoop which conducts random testing with feedback [6], and Gross, et al proposed a genetic algorithm-based approach based on GUI to generate a high coverage test suite while avoiding false failures [7].…”
Section: Related Workmentioning
confidence: 99%
“…Many methods have been proposed to automate various facets of software testing so that the testing cost can be reduced [1]- [7]. However, they only consider information that is available from the software-under-test.…”
Section: Introductionmentioning
confidence: 99%
“…The problem of monitoring sequences of Java method calls is tackled also in [16]. Methodologies that ignore the requirement about method call may generate many tests that fail only because they do not respect the ordering, and such false positives are a burden for testers which must manually discard tests that falsely fail [12]. Coverage: Our methodology is able to give feedback on how much properties are covered (as in LTL 3 ).…”
Section: Introductionmentioning
confidence: 99%